Dopamine-mediated calcium channel regulation in synaptic suppression in L. stagnalis interneurons. Issue 1 (1st January 2018) - Dong, Nancy; Lee, David W. K.; Sun, Hong-Shuo; Feng, Zhong-Ping
ABSTRACT: D2 dopamine receptor-mediated suppression of synaptic transmission from interneurons plays a key role in neurobiological functions across species, ranging from respiration to memory formation. In this study, we investigated the mechanisms of D2 receptor-dependent suppression using soma-soma synapse between respiratory interneuron VD4 and LPeD1 in the mollusk Lymnaea stagnalis (L. stagnalis ). We studied the effects of dopamine on voltage-dependent Ca 2+ current and synaptic vesicle release from the VD4. We report that dopamine inhibits voltage-dependent Ca 2+ current in the VD4 by both voltage-dependent and -independent mechanisms. Dopamine also suppresses synaptic vesicle release downstream of activity-dependent Ca 2+ influx. Our study demonstrated that dopamine acts through D2 receptors to inhibit interneuron synaptic transmission through both voltage-dependent Ca 2+ channel-dependent and -independent pathways. Taken together, these findings expand our understanding of dopamine function and fundamental mechanisms that shape the dynamics of neural circuit.